A review of the engineered treatment of red mud: Construction materials, metal recovery, and soilization revegetation - Kai Jia; Zhenxing Zhou; Shiv Vendra Singh; Chongqing Wang (Results in Engineering, 2024)
Red mud, known as bauxite residue, is an alkaline solid waste generated during alumina production. Globally, the stockpile of red mud is about 3 billion tons and is increasing at a rate of 150 million tons per year. The global production of red mud is mainly distributed in China (28.2 %), Oceania region (22.4 %), South America (14.6 %), Europe (12.9 %), and North America (8.8 %). The increasing stockpile of red mud has posed a huge challenge to safe disposal while restricting the development of the alumina industry. The comprehensive utilization of red mud still needs green, efficient, and massive consumption methods. This work gives a review of the engineered treatment of red mud, including the characteristics and threats, as well as the engineered application through construction materials, metal recovery, and soilization revegetation. For red mud with a high content of metals, resource recovery of valuable metals and rare earth elements is a preferred choice, meeting the circular economy concept. Recovery of valuable metals from red mud can be achieved by magnetic separation, hydrometallurgy, and bioleaching. Hydrometallurgy is promising for recovering valuable metals such as Fe, Al, V, Ti, and rare earth elements, and the recovery is up to 99 %. Construction materials such as cement, geopolymers, and ceramics is an efficient alternative for the massive consumption of red mud, and the high-performance concrete with the compressive strength (129.5 MPa) can be obtained. This strategy is limited by the low price of construction materials, the lowered quality by alkaline components, and potential threats of toxic elements in red mud. Soilization of red mud with ecological restoration is promising for the sustainable management of red mud dam. To accelerate the process of red mud soilization, amendments such as gypsum, organic matter, and microorganisms can be added to neutralize red mud (lowering pH from 10 to 12 to near 7), promote the formation of agglomerates, and provide nutrients, promote the conversion of red mud into soil-like substrate. The phytoremediation of red mud can be realized after effective regulation, finally realizing vegetation establishment of red mud. This work provides technological and practical guidance for the engineered disposal of red mud.